2002
DOI: 10.1039/b204067k
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of thymine and thymidine with ozone

Abstract: The ozonolysis of thymine and thymidine has been investigated by a product study complemented by kinetic studies using spectrophotometry, conductometry and stopped-flow with optical and conductometric detection. Material balance has been obtained. Ozonolysis of thymine (k = 3.4 x 10(4) dm(3) mol(-1) s(-1)) leads to the formation of the acidic (pK(a) = 4) hydroperoxide 1-hydroperoxymethylene-3-(2-oxopropanoyl)urea 5 (similar to34%), neutral hydroperoxides (possibly mainly 1- hydroperoxyhydroxymethyl-3-(2-oxopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…One of the most recent works on DNA degradation with ozone [8] has already reported the secondorder rate degradation rate constant under neutral conditions: 410 L mol −1 s −1 . The work of Von Sonntag and coworkers [8,9] has shown that the ozonization reaction of the free purine and pyrimidine bases depend strongly on their protonation state and hence from the pH of the reaction medium. The reaction velocity increases by several orders of magnitude under alkaline conditions in comparison to acidic conditions [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most recent works on DNA degradation with ozone [8] has already reported the secondorder rate degradation rate constant under neutral conditions: 410 L mol −1 s −1 . The work of Von Sonntag and coworkers [8,9] has shown that the ozonization reaction of the free purine and pyrimidine bases depend strongly on their protonation state and hence from the pH of the reaction medium. The reaction velocity increases by several orders of magnitude under alkaline conditions in comparison to acidic conditions [8].…”
Section: Resultsmentioning
confidence: 99%
“…However, the collapse of the DNA supramolecular structure is even more pronounced in comparison to RNA. The second-order rate constants concerning the reaction between the nucleobases and ozone available from literature [8,9] suggest that the most reactive site in the DNA molecule is offered by the thymine base (rate constant 3.4 × 10 4 L mol −1 s −1 ) followed by guanine base (rate constant 1.6 × 10 4 L mol −1 s −1 ). Cytosine is one order of magnitude less reactive than the former two bases and adenine is even lessreactive three orders of magnitude less than the former two.…”
Section: Chirooptical Properties Of Dna During Ozonolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Much more attention has been dedicated to the ozone degradation of nucleotides and nucleosides (Theruvathu et al, 2001;Flyunt et al, 2002). The ozone degradation of RNA has important implications on the inactivation and destruction of viruses and bacteria by the ozone disinfection and water and wastewater treatment and in the understanding of the mechanism of cell damage in vivo.…”
Section: Ozone Reaction With Rna and Dnamentioning
confidence: 99%
“…Microbial cell damaged and inactivated because the oxidizing action of ozone is directed toward the nucleic acids of these organisms (Flyunt et al 2002). The initial ozone attack is directed against the cell walls with subsequent leakage of cellular content and destruction of the bound DNA, however, ozone is also mutagen and this implies the direct DNA damage (Theruvathu et al 2001).…”
Section: Introductionmentioning
confidence: 99%